Optimalisasi Pembuatan Laporan Keuangan Desa dengan Penggunaan Aplikasi Komputerisasi - Arnita, Vina (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
This study aims to analyze the effect of directing the use of communication applications on improving employee performance in a company. With the development of information technology, digital communication applications have become the main means of facilitating interaction and collaboration between employees. However, the application of these applications is often less than optimal without proper direction. This study used a quantitative approach with an experimental design, where the respondents consisted of 100 employees divided into two groups: an experimental group that was briefed on the intensive use of communication applications and a control group that was not briefed. Data was collected through a survey that measured employee performance before and after the briefing as well as the level of comfort and understanding of the application. The results showed that briefing the use of communication applications can effectively improve employee performance in terms of response speed, team collaboration and task completion. This study suggests the importance of ongoing training and briefings to maximize the benefits of communication apps in the workplace.